Case Report: A case of femoral metastatic cancer misdiagnosed as isolated femoral lesser trochanter avulsion fracture - Pang, Meng-qi; Wu, Feng-ze; Chen, Jia-yan; Zhu, Rang-teng; Jin, Gang; Gong, Wei-jie; Jiang, Han-tao (Frontiers in Oncology, 2025)
ObjectiveTo highlight the diagnostic challenges and clinical implications of metastatic disease presenting as an atypical fracture in a patient with a history of lung cancer, emphasizing the importance of maintaining a high index of suspicion for metastatic disease and the need for comprehensive diagnostic approaches.MethodsWe present a case of a 79-year-old male with a history of poorly differentiated squamous cell carcinoma of the left lung who presented with left hip pain after minor trauma. Initial X-ray and CT imaging suggested an avulsion fracture of the femoral lesser trochanter(LT).The patient was managed conservatively with bed rest. However, persistent pain led to further evaluation with MRI, revealing an underlying pathological fracture due to metastatic cancer.ResultsInitial radiographic and CT findings showed a localized bone defect and surrounding soft tissue swelling, consistent with an avulsion fracture of the LT. However, MRI and contrast-enhanced MRI revealed irregularities in the femoral LT with abnormal bone marrow signals and a prominent soft tissue mass, leading to the diagnosis of a pathological fracture secondary to metastatic cancer. This case underscores the limitations of initial imaging modalities in detecting subtle bone marrow changes and the importance of MRI in identifying metastatic lesions.ConclusionThe misdiagnosis of a pathological fracture as an avulsion fracture can have significant clinical implications, including increased morbidity and delayed treatment of metastatic disease. This case highlights the importance of maintaining a high index of suspicion for metastatic disease, especially in patients with a history of malignancy, and the need for comprehensive diagnostic approaches, including MRI to avoid misdiagnosis. Early recognition and appropriate management of pathological fractures are crucial for improving patient outcomes and quality of life.